"You have got a friend": The value of perceived proximity for teleworking success in dispersed teams. Issue 1 (5th November 2018) - Ruiller, Caroline; Van Der Heijden, Beatrice; Chedotel, Frédérique; Dumas, Marc
Abstract : Purpose: As a way to enable employees to work distantly, teleworking has gained a growing interest in companies. At the same time, management challenges regarding the teleworkers' risk of isolation, coupled with the need to maintain cohesion for the dispersed team, to give an example, are various. How can management practices help to maintain adequate levels of perceived proximity for a dispersed team's members? The purpose of this paper is to answer this question. Referring to a particular person's perception of how close or how far another person is, the concept of perceived proximity is mobilized. This Telecom case study is based on 22 interviews with human resources directors, managers and teleworkers. While the results of this study appear to corroborate empirically the theoretical model as proposed by O'Leary et al. (2014), they also propose nuances, highlighting the importance of the interpersonal relationship to expand the perceived proximity and stressing the need for both distant and face-to-face exchanges. They also help to understand which management practices can influence perceived proximity. In particular, they help to understand the role of communication and collective identity and support the importance of the e-leader. Finally, the results highlight two remote management modes that will be discussed elaborately. Design/methodology/approach: The authors conducted a single in-depth case study of Telecom as a unique case study; it is useful to analyze new and complex phenomena for which theoretical development is emerging and the consideration of the context is essential (Yin, 2013). In total, 22 interviews were conducted with the human resources directors, managers and teleworkers. Lasting between 40 and 130 min each, the interviews were all fully transcribed and analyzed using an iterative thematic content analysis. The authors first manually analyzed the data on the basis of the social regulation theory to interpret the local and the combined regulation (that is say to how the managers and the teleworkers co-build the rules to work being distant) the telework implied between managers, teleworkers and their co-workers (Authors, 2018). Two emerging codes led the authors to reinterpret the data, compared to the initial interpretative framework. The authors thus transformed the coding and recoded the 22 interviews (Bacharach et al., 2000, p. 713; cited by Gibbert et al. 2010, p. 58) around the objective/subjective working time and information and communication technology (ICT) use and the perceived proximity: shared identity and perceived proximity, and communication and perceived proximity. Findings: First, the level of ICT use and the accompanying objective and subjective perceptions with regard to working time are reported and positive perceptions for the employees are determined because of the timing flexibility the ICT determines. Second, the ICT use is presented in relation to the managerial and collegial proximity perceived. Third, the authors discuss the shared identity processes that influence the proximity perceived, followed by the characteristics of the communication process, being the fourth one. As such, the results lead to a valuable input that enables to critically reflect on the e-leader roles, resulting in two emerging management modes seen as a continuum in terms of shared identity: the "e-communicational" mode signals the re-foundation of management in situations of distance based on the personality of the e-leader that influences the team members in terms of communicational and organizational behaviors; and the control management mode that is based upon objectives in a situation of being distant, illustrated by managers who regulate the work made by the distant team in monitoring the objectives without sharing the experience of telework. Research limitations/implications: The results corroborate empirically with the theoretical model by Boyer O'Leary et al. (2014), while putting into perspective the complexity to manage the inter-subjectivity that is related to distance. More specifically, the results show that even if the ICT use leads to a new balance regarding time management for teleworkers – increasing their quality of life perceptions, with a better organizational flexibility – that is to say, a "win-win" configuration, the ultimate success of such a configuration depends on sound management practices. In this sense, the authors propose to enrich their model (Figure 3, p. 33). More extensive research will test two new moderating variables. At first, the results put in evidence the core role of e-management (e-communicational vs control), with a potential moderator effect on the relationship between objective distance and shared identification, on the one hand, and communication, on the other hand. Another result is the potential moderator effect of the ICT use on the relationship between perceived proximity and relationship quality. The nuances proposed support some recent studies arguing that distant communication (versus face-to-face) may inhibit geographically distributed team performance without consideration of the way the teams use ICT to ensure their cohesion and performance (Malhotra and Majchrzak, 2014). Practical implications: These conclusions result into important management recommendations to support dispersed teams with how to cope with challenges such as the risk of delayed communication, possible misinterpretations, limited information richness and great conflicts (Zuofa and Ochieng, 2017). Originality/value: Compared to the unique empirical application of the Boyer O'Leary e t al .'s framework (2014), who found no differences existing in terms of proximity perceived with the study of 341 "geographically present" dyads with 341 "geographically distant, " this study's results show that the construction of the feeling of proximity depends on a fragile balance between virtual and face-to-face exchanges. The authors also highlight the role of an e-leader in this regard and identify and compare two modes of remote management.